Yes we can? white racial framing and the 2008 presidential campaign. - Wingfield, Adia Harvey, 1977- (Routledge, 2010)
This book offers one of the first sociological analyses of Barack Obama?s historic 2008 campaign for the presidency of the United States. Elaborating on the concept of the white racial frame, Harvey Wingfield and Feagin assess the ways racial framing was deployed by principal characters in the 2008 election. This book counters many commonsense assumptions about race, politics, and society, particularly the idea that Obama?s election ushered in a post-racial era. Readers will find this book uniquely valuable because it relies on sound sociological analysis to assess numerous events and aspects of this historic campaign. -- Publisher's description.